Silicon-carbon composite material and preparation method thereof, negative plate, electrochemical device and electronic equipment

By introducing Cu3Si and control pore structure into the silicon negative electrode material of lithium-ion batteries, the problem of volume expansion of silicon negative electrode material is solved, and the structural stability and electrochemical performance of the battery are improved.

CN119275252APending Publication Date: 2025-01-07ENVISION DYNAMICS TECH (JIANGSU) CO LTD +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310836810.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The silicon negative electrode material produces large volume expansion during the cycle, resulting in electrode structure failure and rapid attenuation of capacity. The existing porous design methods have problems with difficult hole size control and unfriendly environment.

Method used

Using silicon-carbon composite materials, Cu3Si is formed by depositing silicon particles and Cu on a carbon substrate, and an open and closed pore structure is formed through heat treatment, which controls the open and closed pore ratio and Cu3Si content to improve the volume buffering and conductivity of the material.

Benefits of technology

The volume buffer space and specific surface area are optimized, the structural stability and dynamic performance of the material are improved, and the first efficiency and cycling performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275252A_ABST
    Figure CN119275252A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material and a preparation method thereof, a negative plate, an electrochemical device and electronic equipment. The silicon-carbon composite material comprises a carbon substrate, silicon particles distributed on the surface of the carbon substrate and a carbon coating layer distributed on the surfaces of the silicon particles and the carbon substrate, wherein the silicon particles comprise silicon and Cu3Si; the content of the Cu3Si is 0.01%-30%, and the percentage is the mass percentage of the Cu3Si in the silicon-carbon composite material; open pores and closed pores are distributed in the silicon-carbon composite material; the ratio of the total volume of the open pores to the total volume of the closed pores is the ratio of the open pores to the closed pores, and the ratio of the open pores to the closed pores is 0.01-100. The silicon-carbon composite material has the structural characteristics that the volume buffer space is large enough and the specific surface area is well controlled, and Cu3Si in the silicon-carbon composite material has good conductivity and ductility, so that the dynamic performance and the structural stability of the silicon-carbon composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet, an electrochemical device and an electronic device. Background Art

[0002] With the rapid development of new energy vehicles, drones, mobile robots and other fields, people have put forward more demands for lithium-ion batteries with higher energy density and greater power density. Silicon anode is considered to be one of the most ideal lithium-ion battery anode materials due to its high theoretical specific capacity, low lithium insertion voltage platform and abundant reserves. However, silicon anode materials will produce large volume expansion during the cycle, causing the electrode structure to fail during long cycles, ultimately leading to rapid capacity decay.

[0003] To address this problem, porous design is one of the most effective solutions. In traditional processes, pores are usually created inside the material by introducing hard templates and soft templates. However, the size of the pores created by these processes is difficult to control, and the process is complicated. They often use processes such as acid washing and water washing, which is not environmentally friendly. To address this problem, some scholars have reported that by introducing some metal elements inside the material, two materials with large differences in thermal diffusion can diffuse with each other under heat treatment conditions, and pores are generated inside. The pore structure can generally be divided into open pores and closed pores. For silicon materials, open pore structures are generally constructed. On the one hand, this can effectively alleviate the large volume expansion of silicon materials during lithium extraction and insertion. However, on the other hand, it will increase the surface area. Although a large surface area can provide a transmission channel for lithium ion transmission, an excessively large surface area will cause a large amount of unstable SEI to grow and cause irreversible loss of lithium ions. Summary of the invention

[0004] In order to overcome the defects of the prior art that silicon negative electrode materials will have a large volume expansion during the cycle, causing the electrode structure to fail during a long cycle, and ultimately leading to a rapid capacity decay, the present invention provides a silicon-carbon composite material and a preparation method, a negative electrode sheet, an electrochemical device and an electronic device. The silicon-carbon composite material of the present invention has a structural characteristic of a sufficiently large volume buffer space and a well-controlled specific surface area, and the Cu3Si in the silicon-carbon composite material has good electrical conductivity and ductility, which is conducive to improving the dynamic performance and structural stability of the silicon-carbon composite material.

[0005] In a first aspect, the present invention provides a silicon-carbon composite material, which comprises a carbon substrate, silicon particles distributed on the surface of the carbon substrate, and a carbon coating layer distributed on the silicon particles and the surface of the carbon substrate;

[0006] Wherein, the silicon particles include silicon and Cu3Si; the content of the Cu3Si is 0.01%-30%, where the percentage is the mass percentage of Cu3Si to the mass percentage of the silicon-carbon composite material;

[0007] The silicon-carbon composite material is distributed with open pores and closed pores; the ratio of the total volume of the open pores to the total volume of the closed pores is the open-closed pore ratio, and the open-closed pore ratio is 0.01-100.

[0008] In a second aspect, the present invention provides a method for preparing a silicon-carbon composite material, characterized in that it comprises the following steps:

[0009] S1, subjecting a precursor of a carbon substrate to a first heat treatment to obtain a carbon substrate;

[0010] S2, depositing a silicon source and Cu on the surface of the carbon substrate to form a precursor of silicon particles to obtain a product 1;

[0011] S3, carbon-coating the product 1 to form a coating layer to obtain a product 2;

[0012] S4, subjecting the product 2 to a second heat treatment to obtain the silicon-carbon composite material; the temperature of the second heat treatment is 600-800°C.

[0013] In a third aspect, the present invention provides a silicon-carbon composite material, which is prepared by the method for preparing the silicon-carbon composite material as described above.

[0014] In a fourth aspect, the present invention provides a negative electrode sheet comprising the silicon-carbon composite material as described above.

[0015] In a fifth aspect, the present invention provides an electrochemical device comprising the negative electrode as described above.

[0016] In a sixth aspect, the present invention provides an electronic device comprising the electrochemical device described above.

[0017] The reagents and raw materials used in the present invention are commercially available.

[0018] The positive and progressive effects of the present invention are:

[0019] The present invention introduces Cu3Si into the silicon-carbon composite material to produce a structure with closed pores and open pores, thereby achieving a structural characteristic of sufficiently large volume buffer space and well-controlled specific surface area, so that the material can exert better structural stability and processing performance. In addition, in addition to effectively improving the ionic conductivity and electronic conductivity of the material, Cu3Si also has good ductility, which is beneficial to improving the dynamics and structural stability of the silicon-carbon composite material. The battery made of the silicon-carbon composite material of the present invention has higher initial efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the structure of silicon-carbon composite material.

[0021] Figure numerals: 1 silicon-carbon composite material, 2 open pore, 3 closed pore. DETAILED DESCRIPTION

[0022] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0023] In the silicon-carbon composite material of the first aspect of the present invention:

[0024] The present invention improves the kinetics and structural stability of the silicon-carbon composite material by quantitatively controlling the Cu3Si content and the open-closed pore ratio in the silicon-carbon composite material structure. The appropriate closed-pore structure can effectively alleviate the large volume expansion of silicon, while the open-pore structure can improve the ion diffusion of the negative electrode material to a certain extent.

[0025] In the present invention, when the content of Cu3Si is less than 0.01%, the metal nanocrystals in the silicon-carbon composite material are too few, the deposited size of silicon is too large, and the element distribution is uneven, resulting in poor effect; when the content of Cu3Si is higher than 30%, the content of active substances such as silicon and carbon in the silicon-carbon composite material is low, which is not conducive to the improvement of gram capacity. Preferably, the content of Cu3Si is 0.01-5%, for example, 2%.

[0026] In some specific embodiments of the present invention, the content of Cu3Si is 2%, 15% and 28%.

[0027] In the present invention, the open pores are pores connected to the outer surface of the silicon-carbon composite material, and gas molecules from the outside can pass into the open pores; the closed pores are pores with a closed structure in the silicon-carbon composite material, and external gas molecules cannot pass into the closed pores.

[0028] In the present invention, when the open-closed pore ratio is less than 1, it indicates that there are more closed pores than open pores in the silicon-carbon composite material, and the closed pore structure is dominant in the structure; when the open-closed pore ratio is greater than 1, it indicates that there are fewer closed pores than open pores in the silicon-carbon composite material, and the open pore structure is dominant in the structure. When the open-closed pore ratio is less than 0.01, it indicates that the structure is mainly a closed pore structure, and the closed pore volume ratio of the silicon-carbon composite material is too high, indicating that the higher the degree of hollowing inside the silicon-carbon composite material, the less beneficial it is to the compaction density of the silicon-carbon composite material; when the open-closed pore ratio is greater than 100, it indicates that there are too few closed pore structures inside the structure, and it is almost a dense structure, which is not conducive to the reservation of a buffer space for volume changes inside the silicon-carbon composite material. Preferably, the open-closed pore ratio is 0.01-50, more preferably 0.1-10, for example 0.2.

[0029] In the present invention, the total volume of the open pores can be measured by conventional methods in the art, preferably by BET.

[0030] In the present invention, the total volume of the closed cells can be measured by conventional methods in the art, preferably by true density.

[0031] Preferably, the method for testing the open-closed cell ratio comprises the following steps:

[0032] S1, calculate the total pore volume of the internal openings of the silicon-carbon composite material by BET test, recorded as V2;

[0033] S2. The Cu mass content is obtained by ICP test, which is recorded as m1; the Si mass content is recorded as m2; the product mass is recorded as M; the true density of the silicon-carbon composite material is tested by a true density tester. The volume V in the test is V1+V3, including the dense volume V1 of the material and the total volume V3 of the closed pores inside the material. The true density is recorded as R, which is calculated as follows:

[0034]

[0035] Where V1 is the compact volume:

[0036] Where ρ1 is the density of Cu, ρ1 = 8.96 g cm -3 ; ρ2 is the density of Si, ρ2 = 2.33 g cm -3 ; ρ3 is the density of C, ρ3 = 2.26 g cm -3 ;

[0037] The total pore volume V3 of closed pores is:

[0038] S3. Calculate the open-closed pore ratio Z, where:

[0039] It should be noted that the order of the above steps S1 and S2 is not critical.

[0040] The present invention can ensure limited film formation on the material surface by limiting the specific surface area, and further ensure the initial coulombic efficiency of the battery. Preferably, the specific surface area of ​​the silicon-carbon composite material is 0.5-10m 2 / g.

[0041] In the present invention, the carbon substrate may be a conventional carbon substrate in the art, preferably a porous carbon material.

[0042] In the present invention, the carbon coating layer preferably comprises one or more of amorphous carbon, graphene-like carbon and polymer carbon.

[0043] In the present invention, the particle size of the silicon particles is preferably nanometer-scale.

[0044] In the present invention, in the silicon-carbon composite material, silicon and carbon are preferably in an amorphous structure.

[0045] In the preparation method of the silicon-carbon composite material of the second aspect of the present invention:

[0046] In the present invention, in step S1, the temperature of the first heat treatment may be a conventional heat treatment temperature in the art, preferably 700-1500°C.

[0047] In the present invention, in step S1, the precursor of the carbon substrate may be a conventional precursor for a carbon substrate in the art, preferably including one or more of graphite, biomass carbon, asphalt carbon, resin carbon and deposited amorphous carbon.

[0048] Wherein, the biomass carbon is preferably coconut shell and / or rice husk.

[0049] Wherein, the resin carbon is preferably phenolic resin.

[0050] In the present invention, in step S2, the deposition temperature is preferably 200-600°C, for example, 250°C.

[0051] In the present invention, in step S2, the deposition pressure is preferably 0.1Pa-2MPa, preferably 1Pa-100kPa, for example 20kPa.

[0052] In the present invention, in step S2, the deposition can be carried out by a conventional deposition method in the art, preferably a liquid phase method.

[0053] In the present invention, in step S2, the silicon source may be a silicon source conventionally used for deposition in the art, preferably one or more of SiH4, SiH3Cl, SiH2Cl2, SiHCl3, SiCl4, SiI4, SiBr4, tetrabutyl silicate and ethyl orthosilicate.

[0054] Preferably, when the silicon source is deposited on the surface of the carbon substrate using the liquid phase method, the silicon source is one or more of SiHCl3, SiCl4, SiI4, SiBr4, tetrabutyl silicate and ethyl orthosilicate, for example, SiHCl3.

[0055] Preferably, the flow rate of the silicon source can be 0.1 mL min -1 -200L min -1 .

[0056] Preferably, the mass of Cu accounts for 0.01-20 wt % of the mass of the silicon source.

[0057] In the present invention, in step S2, the protective gas for deposition is argon and / or nitrogen.

[0058] In the present invention, in step S3, the purpose of the carbon coating is to form a coating layer on the surface of the carbon substrate and the silicon particle precursor so that the carbon layer is deposited and grown inside the open pores, making the interior of the material more dense, and at the same time closing part of the open pore structure to form a closed pore structure.

[0059] In the present invention, in step S3, the temperature of the carbon coating is preferably 400-1000°C, preferably 400-700°C, for example 550°C.

[0060] In the present invention, in step S3, the thickness of the coating layer can be a conventional coating layer thickness in the art, preferably 3-20 nm.

[0061] In the present invention, in step S3, the carbon coating is preferably carried out by chemical vapor deposition.

[0062] Preferably, the carbon-coated carbon source comprises one or more of methane, acetylene and ethylene.

[0063] Preferably, the protective gas for the carbon coating is argon and / or nitrogen.

[0064] In the present invention, in step S4, the purpose of the second heat treatment is to allow the Cu and Si in the structure to fully diffuse to form pores and to form Cu3Si material.

[0065] Preferably, the temperature of the second heat treatment is 600-700°C, for example 650°C.

[0066] Preferably, the protective atmosphere of the second heat treatment is nitrogen and / or argon, for example, nitrogen.

[0067] In the silicon-carbon composite material of the third aspect of the present invention:

[0068] In the present invention, the content of Cu3Si is preferably 0.01-5%.

[0069] In the present invention, in step S3, the coating layer preferably comprises one or more of amorphous carbon, graphene-like and polymer carbon.

[0070] In the present invention, in the silicon-carbon composite material, silicon and carbon are preferably in an amorphous structure.

[0071] In the negative electrode sheet of the fourth aspect of the present invention:

[0072] In the present invention, the negative electrode generally includes a negative electrode material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.

[0073] Wherein, the negative electrode material is as described above.

[0074] The negative electrode conductive agent may be a conductive agent for the negative electrode conventionally selected in the art, preferably one or more of conductive carbon black SP, acetylene black, nano silver powder, carbon nanotubes and graphene, such as acetylene black.

[0075] The negative electrode binder may be a binder for negative electrodes conventionally selected in the art, preferably one or more of vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, sodium carboxymethyl cellulose (SBR) and styrene-butadiene rubber, for example, sodium carboxymethyl cellulose.

[0076] The negative electrode thickener may be a thickener conventionally selected for negative electrodes in the art, preferably CMC.

[0077] In a specific embodiment of the present invention, the preparation method of the negative electrode comprises the following steps: the silicon-based composite material, the conductive agent acetylene black, the thickener CMC and the binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water as a solvent is added, and the mixture is fully stirred to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and a negative electrode sheet is prepared through drying, cold pressing, slitting and other processes.

[0078] In the electrochemical device of the fifth aspect of the present invention:

[0079] In the present invention, the electrochemical device can generally be a conventional device in the art containing the negative electrode as described above, such as a battery, a capacitor, etc. Wherein, the battery preferably includes a primary battery or a secondary battery, and the secondary battery is, for example, a lithium ion battery or a sodium ion battery.

[0080] In some preferred embodiments, the electrochemical device is a lithium ion battery. The lithium ion battery generally comprises the negative electrode, the positive electrode, an electrolyte and a separator.

[0081] In the present invention, the positive electrode may be a positive electrode conventionally used in lithium-ion secondary batteries in the art, which generally includes a positive electrode material, a positive electrode conductive agent and a positive electrode binder.

[0082] The positive electrode material may be a material conventionally selected for positive electrode in the art, including but not limited to one or more of lithium iron phosphate, lithium iron manganese phosphate, ternary positive electrode material and lithium-rich manganese-based material.

[0083] The positive electrode conductive agent may be a conductive agent for positive electrode conventionally selected in the art, preferably one or a mixture of conductive carbon black SP, acetylene black, nano metal powder, carbon nanotube and graphene, such as conductive carbon black SP.

[0084] The positive electrode binder may be a binder conventionally selected for positive electrodes in the art, preferably one or a mixture of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose SBR and styrene-butadiene rubber, such as polyvinylidene fluoride.

[0085] In a specific embodiment of the present invention, the positive electrode is prepared by the following method: the positive electrode material, the positive electrode conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed according to a weight ratio of 97:1.5:1.5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector aluminum foil, and a positive electrode sheet is prepared through processes such as drying, cold pressing, and slitting.

[0086] In the present invention, the electrolyte may be an electrolyte conventionally used for lithium-ion batteries in the art, generally comprising a non-aqueous solvent, a lithium salt and an additive.

[0087] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).

[0088] Wherein, the lithium salt can be conventional lithium salt in the art, preferably LiPF6, LiBF4, LiN(SO2F)2(LiFSI), LiClO4, LiAsF6, LiB(C2O4)2(LiBOB), LiBF2(C2O4)(LiDFOB), LiN(SO2R F )2. LiN(SO2F)(SO2R F ), preferably LiPF6.

[0089] The content of the lithium salt in the electrolyte is preferably 5%-20%, where the percentage is the percentage of the lithium salt to the total mass of the electrolyte.

[0090] Among them, the additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), diethyl sulfate (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.

[0091] The dosage of the additive may be a conventional dosage in the art, preferably 1%-4%, for example 2%, where the percentage is the percentage of the additive to the total mass of the electrolyte.

[0092] In the present invention, the electrolyte can be prepared by conventional methods in the art, preferably including the following steps: in an argon atmosphere glove box with a water content of <10 ppm, a fully dried lithium salt is dissolved in a solvent, and the electrolyte is obtained after mixing evenly.

[0093] In a specific embodiment of the present invention, the preparation of the electrolyte includes the following steps: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0094] In the present invention, the separator may be a porous membrane, preferably a polypropylene separator (PP).

[0095] In the present invention, the thickness of the isolation film is preferably 9-18 μm, such as 11 μm.

[0096] In the present invention, the air permeability of the isolation membrane is 180 s / 100 mL to 380 s / 100 mL.

[0097] In the present invention, the porosity of the isolation membrane is 30% to 50%.

[0098] In a preferred embodiment of the present invention, the preparation of the lithium-ion secondary battery comprises the following steps: stacking the prepared positive electrode, the separator, and the negative electrode in sequence, with the separator being located between the positive electrode and the negative electrode to play an isolating role, then wrapping with an aluminum-plastic film, and injecting the electrolyte after drying, and then undergoing packaging, standing, and forming processes.

[0099] In the electronic device of the sixth aspect of the present invention:

[0100] In the present invention, the electronic device may generally include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.

[0101] The mobile device is preferably a mobile phone or a laptop computer. The electric vehicle preferably includes a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, and an electric truck.

[0102] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0103] Examples 1-8 and Comparative Examples 1-4

[0104] The silicon-carbon composite material provided by the present invention comprises three parts: a carbon substrate, a nano-silicon material and a surface coating layer, and a porous silicon-carbon structure is prepared by a liquid phase method;

[0105] The preparation method of the silicon-carbon composite material comprises the following steps:

[0106] Step S1, subjecting a precursor of a carbon substrate to a first heat treatment to prepare a carbon substrate;

[0107] Step S2, depositing a silicon source on the surface of a carbon substrate by a liquid phase method, controlling the deposition pressure during the deposition process, and controlling the pressure to 0.1Pa-2MPa. The deposited silicon source is SiHCl3, SiCl4, SiI4, SiBr4, tetrabutyl silicate, ethyl orthosilicate, SiH4, SiH2Cl2, and the deposition temperature is controlled at 200-600°C. During the synchronous deposition process, Cu is introduced into the reaction system to form a precursor of silicon particles, which is recorded as product 1. The flow rate of the silicon source is controlled at 0.1mL min -1 -200L min -1 , the mass of Cu accounts for 0.01-10wt% of the mass of the silicon source;

[0108] Step S3, carbon-coating the surface of product 1 by vapor deposition to obtain product 2, wherein the carbon source is one or more of methane, acetylene and ethylene, the protective gas is nitrogen, and the temperature of carbon coating is controlled at 400-1000° C.;

[0109] Step S4, subjecting the product 2 to a second heat treatment to obtain a silicon-carbon composite material, wherein the temperature of the second heat treatment is controlled at 600-800°C, and the protective atmosphere is nitrogen; wherein the parameters of the deposition, carbon coating and second heat treatment are as shown in Table 1.

[0110] Table 1 Process parameters for preparing silicon-carbon composite materials in Examples 1-8 and Comparative Examples 1-4

[0111]

[0112]

[0113] Effect Example 1

[0114] The silicon-carbon composite material prepared in Example 1 was subjected to Raman and XRD tests.

[0115] The Raman spectrum of the silicon-carbon composite material obtained in Example 1 is in the range of 500-520 cm -1 There is no characteristic diffraction peak of crystalline silicon at 490-500cm -1 There is a characteristic peak, which corresponds to the characteristic diffraction peak of amorphous silicon.

[0116] The XRD spectrum of the silicon-carbon composite material prepared in Example 1 has no obvious crystal diffraction peak.

[0117] The above results indicate that both silicon and carbon in the silicon-carbon composite material prepared in Example 1 are amorphous.

[0118] Effect Example 2

[0119] (1) Preparation of lithium-ion secondary batteries

[0120] ① Preparation of positive electrode

[0121] The positive electrode material, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.5:1.5, and the solvent N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through processes such as drying, cold pressing, and slitting.

[0122] ② Preparation of negative electrode

[0123] The silicon-based composite materials prepared in Examples 1-8 and Comparative Examples 1-4 were used as negative electrode materials, acetylene black as a conductive agent, CMC as a thickener, and SBR as a binder in a mass ratio of 96:4:1:1.2:1:4, and deionized water as a solvent was added, and the mixture was fully stirred to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and a negative electrode sheet was prepared through processes such as drying, cold pressing, and slitting.

[0124] ③ Preparation of electrolyte

[0125] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0126] ④ Preparation of diaphragm

[0127] A PE porous membrane is used as a separator; a polyethylene (ie, PE) porous membrane with a thickness of 11 μm, an air permeability of 280 s / 100 mL, and a porosity of 40% is used as a separator

[0128] ⑤Preparation of lithium-ion secondary batteries

[0129] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, the aluminum plastic film is wrapped, and after drying, the above-prepared electrolyte is injected. After packaging, standing, formation and other processes, a soft-pack battery (i.e., lithium-ion secondary battery) with a capacity of 1Ah is finally prepared.

[0130] (2) Test part

[0131] ① Test the initial efficiency and cycle performance of each button cell produced. The specific steps are: cycle with a charge and discharge program of 0.1C to 1.5C and 0.1C to 5mV, according to the following formula:

[0132] First efficiency = first week charging capacity in grams / first week discharging capacity in grams * 100%;

[0133] Among them, the first week charging capacity = first week charging capacity / (negative electrode sheet mass * 0.8);

[0134] The first week discharge capacity in grams = first week discharge capacity / (negative electrode mass*0.8).

[0135] And the battery is cycled in the same manner under the same conditions. When the SOH is 80%, the corresponding number of cycles is the cycle performance of the battery. 80% SOH is defined as the ratio of the discharge capacity of the battery after the cycle to the discharge capacity of the first cycle is 80%.

[0136] ②TG test

[0137] Tested according to GB / T 31984-2015.

[0138] ③BET test

[0139] Tested according to GB / T 39713-2020.

[0140] ④ICP test

[0141] Tested to BS EN ISO 14720-2-2013.

[0142] Table 2 Initial efficiency and cycle performance of silicon-carbon composite materials obtained in Examples 1-8 and Comparative Examples 1-4

[0143] <![CDATA[Cu3Si content]]> Open / Closed Cell Ratio First coulombic efficiency / % Cycle performance / cycle Example 1 2% 0.5 94.3 1420 Example 2 15% 10 93.3 1120 Example 3 28% 100 89.3 890 Example 4 0.01% 0.15 93.2 1210 Example 5 2% 12 93.0 1050 Example 6 2% 95 90.2 760 Example 7 2% 0.3 93.2 1060 Example 8 2% 0.9 93.1 1120 Comparative Example 1 0 1000 83.1 250 Comparative Example 2 40% 100 80.1 650 Comparative Example 3 2% 30 81.2 580 Comparative Example 4 2% 50 83.2 680

[0144] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material obtained in Example 1. According to Table 2, by comparing Example 1 with Comparative Example 1, it can be seen that when Cu is not introduced during the preparation of the silicon-carbon composite material, that is, the silicon-carbon composite material does not contain Cu3Si, the open-closed pore ratio of the silicon-carbon composite material is 1000, which indicates that the silicon-carbon composite material obtained in Comparative Example 1 has too few closed-pore structures inside the structure, and is almost a dense structure. The electrochemical performance of the lithium-ion battery made from the silicon-carbon composite material is worse than that of Example 1, and its first coulombic efficiency is only 83.1%, and the number of cycles is only 250.

[0145] By comparing Example 1 and Comparative Example 2, it can be seen that when excessive Cu is introduced during the preparation of the silicon-carbon composite material, the Cu3Si content in the obtained silicon-carbon composite material is too high, and the Cu3Si content of Comparative Example 2 is specifically 35%. Even if the open and closed pore ratio of the obtained silicon-carbon composite material is 100, the electrochemical performance of the lithium-ion battery made from the silicon-carbon composite material is still poor, with an initial coulombic efficiency of 80.1% and a cycle number of only 650, both of which are much lower than Example 1.

[0146] It can be seen from Examples 1-2 and 4 that when preparing a silicon-carbon composite material, the mass of the introduced Cu accounts for 0.01-15wt% of the mass of the silicon source, and the open-closed pore ratio of the silicon-carbon composite material is between 0.5-100. The lithium-ion battery prepared from the silicon-carbon composite material has a higher first coulomb efficiency, specifically between 93.2-94.3%, and the cycle performance is also significantly improved, and the number of cycles of 80% SOH is 1120-1420. This is because the amount of Cu introduced will affect the content of Cu3Si in the silicon-carbon composite material, and when the content of Cu3Si is too low, the metal nanocrystals in the silicon-carbon composite material are too few, the deposition size of silicon is too large, and the element distribution is uneven, resulting in poor effect. When the content of Cu3Si is too high, the content of active substances such as silicon and carbon in the silicon-carbon composite material is low, which is not conducive to the improvement of gram capacity. Only by introducing a suitable amount of Cu can the deposition size of silicon be controlled, and the elements can be evenly distributed, and the content of active substances such as silicon and carbon in the silicon-carbon composite material is not reduced, and the gram capacity of the material is significantly improved.

[0147] It can be seen from Examples 1 and 5-6 that when preparing a silicon-carbon composite material, the deposition pressure is between 0.1Pa-20kPa, and the lithium-ion battery made from the silicon-carbon composite material has a higher first coulombic efficiency, specifically between 93.0-94.3%, and the cycle performance is also significantly improved, with the number of cycles of 80% SOH being between 1050-1420. This is because the deposition pressure affects the particle size and distribution of silicon particles deposited on the surface of the material, further affecting the first coulombic efficiency and cycle performance of the silicon-carbon composite material.

[0148] It can be seen from Example 1, Examples 7-8 and Comparative Examples 3-4 that when preparing a silicon-carbon composite material, the temperature of the second heat treatment is between 600-800°C, and the first coulombic efficiency and cycle stability of the lithium-ion battery made from the silicon-carbon composite material are both good, the first efficiency is above 89.3%, and the number of cycles of 80% SOH is above 760. When the temperature of the second heat treatment is 400°C or 900°C, the first coulombic efficiency and cycle performance of the lithium-ion battery made from the silicon-carbon composite material are significantly reduced. This is because the temperature of the second heat treatment affects the full diffusion of Cu and Si in the structure, affects the open and closed pore ratio of the silicon-carbon composite material, and further affects the first coulombic efficiency and cycle performance of the silicon-carbon composite material.

[0149] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A silicon-carbon composite material, characterized in that: It includes a carbon substrate, silicon particles distributed on the surface of the carbon substrate, and a carbon coating layer distributed on the silicon particles and the surface of the carbon substrate; Wherein, the silicon particles include silicon and Cu3Si; the content of the Cu3Si is 0.01%-30%, where the percentage is the mass percentage of Cu3Si to the mass percentage of the silicon-carbon composite material; The silicon-carbon composite material is distributed with open pores and closed pores; the ratio of the total volume of the open pores to the total volume of the closed pores is the open-closed pore ratio, and the open-closed pore ratio is 0.01-100.

2. The silicon-carbon composite material according to claim 1, characterized in that: The silicon-carbon composite material meets one or more of the following conditions: (a) the content of Cu3Si is 0.01%-5%; (b) the open-closed pore ratio of the silicon-carbon composite material is 0.01-50; (c) The specific surface area of ​​the silicon-carbon composite material is 0.5-10m 2 / g; (d) The carbon coating layer comprises one or more of amorphous carbon, graphene-like carbon and polymer carbon.

3. The silicon-carbon composite material according to claim 1, characterized in that: The carbon substrate is a porous carbon material.

4. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, subjecting a precursor of a carbon substrate to a first heat treatment to obtain a carbon substrate; S2, depositing a silicon source and Cu on the surface of the carbon substrate to form a precursor of silicon particles to obtain a product 1; S3, carbon-coating the product 1 to form a coating layer to obtain a product 2; S4, subjecting the product 2 to a second heat treatment to obtain the silicon-carbon composite material; the temperature of the second heat treatment is 600-800°C.

5. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The method for preparing the silicon-carbon composite material meets one or both of the following conditions: (e) the deposition temperature is 200-600° C.; (f) the deposition pressure is 0.1Pa-2MPa; (g) the temperature of the carbon coating is 400-1000°C; (h) The flow rate of the silicon source is 0.1 mL min -1 -200L min -1 ; (i) The mass of Cu accounts for 0.01-20 wt % of the mass of the silicon source.

6. The method for preparing the silicon-carbon composite material according to any one of claims 4 to 5, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: (j) the precursor of the carbon substrate comprises one or more of graphite, biomass carbon, pitch carbon, resin carbon and deposited amorphous carbon; (k) the deposition is carried out by a liquid phase method; (l) the silicon source is one or more of SiH4, SiH3Cl, SiH2Cl2, SiHCl3, SiCl4, SiI4, SiBr4, tetrabutyl silicate and ethyl orthosilicate; (m) The carbon-coated carbon source includes one or more of methane, acetylene and ethylene.

7. A silicon-carbon composite material, characterized in that: It is prepared by the preparation method of the silicon-carbon composite material according to any one of claims 4 to 6, Wherein, the content of Cu3Si in the silicon-carbon composite material is 0.01-30%.

8. A negative electrode sheet, characterized in that: It comprises the silicon-carbon composite material as claimed in any one of claims 1 to 3 and 7.

9. An electrochemical device, characterized in that: It comprises the negative electrode sheet as claimed in claim 8.

10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 9.